Mechanochemical synthesis of bismuth-based anion exchange materials to immobilize arsenic pollution - Prospects for advanced treatment of anion-containing wastewater. (15th March 2022) - Wang, Chao; Hu, Huimin; Chen, Min; Wang, Qian; Liu, Chang; Chen, Mengfei; Yan, Shanshan; Zhang, Qiwu
Abstract: Many types of anionic pollutants exit in the aqueous environment including the group containing halogen (F-, I-, IO3 -, BrO3 -, ClO3 − ), the group containing heavy metals (VO4 3−, AsO3 3−, CrO4 2−, AsO4 3− ), and eutrophic elements resulting from agricultural, aquacultural, urban and industrial activities (NO3 −, PO4 3− ). Except for layered double hydroxide, anionic exchangeable resin, few choices are available to work for the treatment of the anionic pollutants. In this study, a new type of anion exchangeable compound was reported as an alternative. Sulfate-based layered bismuth oxide with the formula of Bi2 O(OH)2 SO4 as a clear crystalline phase was prepared simply by ball milling Bi oxide and sulfate together. Several analytical methods such as XRD, XPS, FTIR were used to characterize the products after the As (V) adsorption to understand the ions exchange mechanism. The excellent performance to fix arsenate anion reaching over 99.9% of As(V) removal percentage with Bi2 O(OH)AsO4 as adsorption product was understood probably due to the synergistic effect of several exchangeable anions inside the prepared sample. This research may open a promising way to effectively remove toxic and harmful anions by the newly prepared anion exchangeable materials. Graphical abstract: The mechanism to remove As (V) pollutant. Image 1 Highlights: ➢ Active Bi2 O(OH)2 SO4 synthesized by milling for effective As (V) fixation. ➢ Improvement of drinking water arsenic concentration standards ➢ Highly efficient sulfate-based layered bismuth oxide for anion exchange ➢ Prospects for advanced treatment of anion-containing wastewater